POLITICAL MONEY IN THE IMPLEMENTATION OF ELECTION IN INDONESIA - Afifa Rangkuti (NOMOI Law Review, 2021)
Politicalmoney(Money Politicsarea forms of abuse, politik money can be done bygranting the form of money or goods such as food to the peoplein order for them to vote forthe partyconcernedatau may also mean vote-buying in the political process and power and the act of handing out money either privately or by a party to influence the voter's vote(voters.Among the forms of activities that are consideredmoney politics include: a Dthe distribution of donations in the form of goods or money to party cadres, cheerleaders,certaingroups or groups, bContributions from conglomerates or businessmen for the interests of certain political parties, withillegal concessions, cMisuse of authority and facilities the state for the benefit of and or inviting sympathy for certain political parties, for example the misuse of JPS funds or the misuse ofcheap KUT credit and others.In Law No. 7 of 2017 concerning Elections Article 1 point 1 that Elections are ameans of people's sovereignty to elect members of the DPR, DPD members, the President and vice-president and to elect members of the DPRD which are carried out directly, publicly, freely, confidentially, honestly and fairly. in the unitary state of the Republic of Indonesia based on Pancasila and the 1945 Constitution.Thus, elections are an important means for the people in the life of the state, namely by electing their representatives who in turn will control the wheels of government.However, inreality, fewpeople are aware of the importance of thecommunity'srolein elections.As a result, it is difficult to prove the practiceofmoney politics,thusmaking thecandidates who will be electedfreelypracticemoney politicswith the aim of gettingthemostvotesin the implementation ofthe election.Keywords:Political Money,Implementation,Election.